دراسة بيولوجيا التكاثر عند سمك القجاج (Sparus aurata L.) في الساحل السوري. - حمود, فينا; منصور, كاترين; بالوش, زويا (Latakia University Journal -Biological Sciences Series, 2016)
أُجريت هذه الدراسة على النوع Sparus aurata (Sparidae)، والذي تم اصطياده من عدة مناطق على امتداد الساحل السوري، خلال الفترة الممتدة بين آذار 2012وشباط 2014، وقد بلغ عدد الأفراد (297) فرداً تراوحت أطوالها الكلية بين (31-15)سم وأوزانها الكلية بين(410.34-53.1)غ. أظهرت دراسة مؤشر النضج الجنسي (GSI) أن فترة التكاثر تقع بين تشرين الثاني وشباط بالنسبة للذكور والإناث، مع ذروة نضج واضحة في شهر كانون الثاني (3.98±0.97)% للإناث وفي شهر كانون الأول(2.19±0.29)% للذكور، وأن الطول عند أول نضج جنسي هو (21.5،22.5) سم للذكور والإناث على التوالي. وكانت نتائج مؤشر وزن الكبد النسبي (HSI)متوافقة مع التغيرات البيئية المحيطة والتغيرات الفيزيولوجية الناتجة عن تغير النشاط الجنسي خلال دورة التكاثر. كما أظهرت دراسة الخصوبة مجالاً واسعاً للمجموعات الطولية المدروسة، وكانت علاقة الخصوبة المطلقة مع كل من الطول الكلي والوزن الكلي علاقة خطية، وتراوحت الخصوبة النسبية بين (567896- 849362) بيضة لكل 1كغ من وزن الجسم. أظهرت دراسة التوزع التكراري لأقطار البيوض وجود قمة واحدة في منحني التوزع، وتراوحت أقطار البيوض خلال موسم التكاثر بين (0.05-0.3) مم. This study has been done on Sparus aurata (Sparidae). Fish samples (297 individuals) were collected along the Syrian Coast from March 2012 to February 2014. Total length (T) was 15 - 31 cm, and the total weight (W) was 53,1 - 410,34 g. The study of gonado somatic index (GSI) showed that the reproduction period was between November and February with a maturity peak in January (3.98±0.97)% for females ,and in December (2.19±0.29)% for males. In addition, the length at the first sexual maturity was (21.5 cm) and (22.5 cm) for males and females respectively. The results of the hepato somatic index (HSI) was compatible with the surrounding environmental and physiological changes which resulted from the change of sexual activity during the reproductive cycle. Fecundity showed a wide range for a given length, there was a linear relationship between the absolute fecundity and each of length groups and total weight. Relative fecundity was (567896-849362) egg per 1kg body weight. The frequency distribution of eggs diameters revealed the presence of one peak, and the eggs diameter during the reproduction period ranged from 0.05 to 0.3mm.